Energy Savings Potential in Using Cold-shelves Innovation for Multi-deck Open Front Refrigerated Cabinets. (March 2019) - Tsamos, Konstantinos M.; Mroue, Hassan; Sun, Jining; Tassou, Savvas A; Nicholls, Nobby; Smith, Graham
Abstract: An approach considered in recent years to improve the efficiency of open-type refrigerated display cabinets is to install air guiding strips at the front face of the shelves with a single layer air curtain. This paper presents experimental results comparing a conventional open-type vertical refrigerated cabinet and a cold shelf innovation, which integrates both air-guiding strips and air supply at the front of individual shelves. In addition, a comprehensive and detailed Computational Fluid Dynamics model using ANSYS Fluent has been created to further investigate the influence of the cold shelve innovation on the performance of vertical multi-deck refrigerated display cabinets. The experimental results showed energy savings of 16.7 kWh/24 hrs for the guiding strips and cold shelf innovation compared to the conventional cabinet due to the more efficient air curtain and lower air temperature entering the evaporator coil.